A Systematic Review of Micropulse Laser Trabeculoplasty (MLT) in Primary Open-Angle Glaucoma (POAG) Management: Efficacy, Safety, and Future Perspectives - Filippo Confalonieri; Barbara Casarini; Annalaura Papapicco; Fabio Stiro; Raffaele Piscopo; Luca D’Andrea; Goran Petrovski; Tommaso Verdina (Biomedicines)
Background/Objectives: Micropulse laser trabeculoplasty (MLT) is gaining attention as a non-invasive treatment option for primary open-angle glaucoma (POAG), offering an alternative to traditional surgeries and medications. This systematic review evaluates the effectiveness, safety, and potential of MLT in glaucoma management. Methods: This review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The strength of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology, following the 2011 Oxford Centre for Evidence-Based Medicine (OCEBM) recommendations. Results: We identified 79 articles, and after removing duplicates and screening abstracts, 56 articles were eligible for further review. A detailed full-text analysis was conducted on 26 articles, of which 15 met the predefined inclusion criteria. Conclusions: MLT shows promise as a primary or adjunctive treatment for reducing intraocular pressure (IOP) in glaucoma and ocular hypertension patients. Current evidence supports its efficacy and safety; however, additional long-term studies are needed to confirm its durability and compare its effectiveness with traditional surgical and pharmacological approaches. Standardizing treatment protocols and refining patient selection criteria could enhance MLT’s clinical value and support its broader adoption in glaucoma care.